2016
DOI: 10.1080/03630242.2016.1157125
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between perceived perinatal stress and depressive symptoms, anxiety, and parental self-efficacy in primiparous mothers and the role of social support

Abstract: The aim of the authors in this study was to evaluate the relationships between perceived perinatal stress and social support to psychological health outcomes in mothers. A longitudinal, quantitative study was conducted in Geneva, Switzerland on 235 primiparous mothers from September 2010 to January 2012. Data were collected between gestational weeks 37 and 41 (T1), 2 days post-delivery (T2), and at 6 weeks postpartum (T3). Perinatal stress was associated with depressive symptoms (R = 0.223), anxiety (R = 0.242… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 42 publications
8
60
2
1
Order By: Relevance
“…Only the bivariate analysis showed that adolescents who lacked social support (total) did not have lower PME, a result that is in line with previous studies of adults (Razurel, Kaiser, Antonietti, Epiney, & Sellenet, 2017). However, in the hierarchical analysis, once depressive symptomatology was introduced into the model, it became more important and social support was no longer significant.…”
Section: Discussionsupporting
confidence: 85%
“…Only the bivariate analysis showed that adolescents who lacked social support (total) did not have lower PME, a result that is in line with previous studies of adults (Razurel, Kaiser, Antonietti, Epiney, & Sellenet, 2017). However, in the hierarchical analysis, once depressive symptomatology was introduced into the model, it became more important and social support was no longer significant.…”
Section: Discussionsupporting
confidence: 85%
“…Flach et al found in a large birth cohort that antenatal domestic violence, measured by two questions about whether a woman's partner had been emotionally cruel or physically hurt them, was associated with increased depressive symptoms across pregnancy and the postpartum using the Edinburgh Postnatal Depression Scale but also did not examine how this might have impacted on parenting (Flach et al, 2011). In order to consider the potentially protective factors in early parenting, investigators have consider the role of social support and the quality of the marital/partner relationship and its capacity to moderate risk factors such as depression and trauma (Gelfand, Teti, & Radin Fox, 1992;Razurel, Kaiser, Antonietti, Epiney, & Sellenet, 2017;Taraban et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As women gain knowledge of newborn care and infant development and growth, they also learn parental roles and responsibilities. Therefore, it is critical that healthcare professionals assist women after birth (Razurel, Kaiser, Antonietti, Epiney, & Sellenet, 2017).…”
Section: Introductionmentioning
confidence: 99%